Proper NMR methods for studying RNA thermometers - 김원제; 김낙균 (한국자기공명학회, 2015)
In some pathogenic bacteria, there are RNA thermometers, which regulate the production of virulence associated factors or heat shock proteins depending on temperature changes. Like a riboswitches, RNA thermometers are located in the 5’-untranslated region and involved translational gene regulatory mechanism. RNA thermometers block the ribosome-binding site and start codon area under the 37℃ within their secondary structure. After bacterial infection, increased the temperature in the host causes conformations changes of RNA, and the ribosome-binding site is exposed for translational initiation. Because structural differences between open and closed forms of RNA thermometers are mainly mediated by base pairing changes, NMR spectroscopy is a very useful method to study these thermodynamically changing RNA structure. In this review, we briefly provide a fundamental function of RNA thermometers, and also suggest a proper NMR experiments for studying RNA thermometers.